Citizen science in China's water resources monitoring: current status and future prospects. Issue 3 (3rd April 2022) - Wu, Yaqian; Washbourne, Carla; Haklay, Muki
ABSTRACT: The global challenges of sustainability are encapsulated in the UN Sustainable Development Goals (SDGs), to which 193 member states are committed. However, a key challenge remains in identifying appropriate methods, indicators, and the ability to monitor progress towards these 2030 Agenda goals. Citizen Science (CS), as a scientific activity in which non-professionals voluntarily participate and cooperate with experts, has been used in Western countries to meet this challenge. Whether it also applies to achieving the SDGs of Asian countries like China is a question that needs to be answered with evidence. On this basis, the tasks of this study are twofold: first, through a literature review, we identify CS projects relevant to water that are happening in China; Second, we analyse the selected projects from three dimensions (scientific, participant, socio-ecological and economic) under an adjusted CS evaluation framework to determine their suitability in China. The results show that at least 19 water-related citizen science projects emerged in China since 2005, most of which are dedicated to improving water quality, with a few focusing on biodiversity monitoring. Multiple stakeholders, including non-governmental (NGO)/non-profit (NPO) organisations, academic institutions, governments and companies participate in these activities, with NGOs accounting for the most. CS has not expanded rapidly in the past 15 years, but most of the projects are still active, which shows the possibility of CS's further development in China after a good strategic framework has been formulated.